2020
DOI: 10.1186/s13072-020-00335-x
|View full text |Cite
|
Sign up to set email alerts
|

Linker histone variant H1t is closely associated with repressed repeat-element chromatin domains in pachytene spermatocytes

Abstract: Background: H1t is the major linker histone variant in pachytene spermatocytes, where it constitutes 50-60% of total H1. This linker histone variant was previously reported to localize in the nucleolar rDNA element in mouse spermatocytes. Our main aim was to determine the extra-nucleolar localization of this linker histone variant in pachytene spermatocytes. Results: We generated H1t-specific antibodies in rabbits and validated its specificity by multiple assays like ELISA, western blot, etc. Genome-wide occup… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 81 publications
(102 reference statements)
0
10
0
Order By: Relevance
“…Numerous studies have identified H1T2 as a critical testes-specific histone H1 for spermiogenesis, lack of which results in reduced fertility because of delayed nuclear condensation and aberrant elongation characterized by acrosome detachment and fragmented DNA [ 22 ]. With this background, we were curious to gain more insights into the genomic functions of H1T2 in the context of our recent studies on the other two testes-specific histone variants, H1t and HILS1 [ 24 , 25 ].
Fig.
…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Numerous studies have identified H1T2 as a critical testes-specific histone H1 for spermiogenesis, lack of which results in reduced fertility because of delayed nuclear condensation and aberrant elongation characterized by acrosome detachment and fragmented DNA [ 22 ]. With this background, we were curious to gain more insights into the genomic functions of H1T2 in the context of our recent studies on the other two testes-specific histone variants, H1t and HILS1 [ 24 , 25 ].
Fig.
…”
Section: Resultsmentioning
confidence: 99%
“…Earlier studies from our laboratory had analyzed the epigenetic status of the LINE repeats at different stages of spermatogenesis in the context of linker histones occupancy. In pachytene spermatocytes, H1t decorates the methylated LINE and LTR repeats in addition to heterochromatin repressive marks [ 25 ]. As the sperm differentiation progresses through histone hyper acetylation and incorporation of other histone variants, HILS1 gets incorporated to provide a more loosened chromatin to facilitate the histone replacement, still maintaining the repressed chromatin architecture of the majorly bound LINE repeats [ 24 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations